Information and Communication Technologies in Tourism 2014 Proceedings of the International Conference in Dublin, Ireland, January 21-24, 2014 - Xiang, Zheng; Tussyadiah, Iis.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
The papers presented in this volume advance the state-of-the-art research on social media and Web 2.0, electronic tourism marketing, website development and evaluation, search engine marketing and optimization, IT adoption and diffusion, virtual travel communities, mobile technologies, management information systems in tourism, eLearning, recommender systems for tourism businesses and destinations and electronic distribution for hospitality and travel products. This book covers the most significant topics contributed by prominent scholars from around the world and is suitable for both academics and practitioners who are interested in the latest developments in e-Tourism.
Mobile Technologies and Context-Aware Systems -- Social Media Marketing Strategies -- Emotion and Sentiment Analyses -- Social Network and Interaction -- Online Reviews -- ICT and Travellers' Behaviour -- Gaming, Gamification and Smart Tourism -- Website Evaluation -- ICT Adoption -- eLearning -- Distribution and Decision Support Systems.
Keywords: Economics; Social sciences -- Data processing; Architecture; Marketing; Management information systems; Economics/Management Science; Business Information Systems; e-Commerce/e-business.; Computer Appl. in Social and Behavioral Sciences; Marketing; Information Systems Applications (incl. Internet).; Cities, Countries, Regions